2016
DOI: 10.1039/c5ra21184k
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistive gas sensor for the sensitive detection of nitrogen dioxide based on nitrogen doped graphene nanosheets

Abstract: Nitrogen doped graphene nanosheet coated interdigitated electrodes for sensitive detection of NO2 gas at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…As shown in Figure 5, the N-doped graphene exhibited good sensitivity to NO 2 . This was expected, as Shaik et al reported NO 2 sensing with N-doped graphene, which was fabricated using a wet process and exhibited p-type behavior [63]. In contrast, the theoretical studies of Jappor et al and Dai et al [64,65], which focused on quaternary N-doping, indicated that NO 2 was weakly physiosorbed onto the N-doped graphene surface.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure 5, the N-doped graphene exhibited good sensitivity to NO 2 . This was expected, as Shaik et al reported NO 2 sensing with N-doped graphene, which was fabricated using a wet process and exhibited p-type behavior [63]. In contrast, the theoretical studies of Jappor et al and Dai et al [64,65], which focused on quaternary N-doping, indicated that NO 2 was weakly physiosorbed onto the N-doped graphene surface.…”
Section: Resultsmentioning
confidence: 97%
“…A nylon window screen film (15 cm × 15 cm, oxygen plasma pretreatment) coated on the aluminum foil was employed as the collector, which was placed 15 cm away from the syringe needle. The feeding rate of the solution was 0.5 mL/h, and the applied potential between the needle and collector was 20 KV [ 14 , 19 ]. After electrostatic spinning for different time periods, the PAN-coated nylon window screens were collected as 3D scaffolds and dried at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Chemically modified graphene films have good sensing performances to different concentrations of NO 2 , from 15 to 115 ppm [ 18 ]. The nitrogen-doped graphene nanosheet-based sensors demonstrated a high sensing response to NO 2 , from 2.5 to 100 ppm [ 19 ]. However, there are seldom reports for ultrasensitive sensors that detect lower concentrations of NO 2 (10–200 ppb).…”
Section: Introductionmentioning
confidence: 99%
“…To experimentally confirm some of the above-mentioned theoretical predictions, various doped graphene materials have been synthesized and evaluated as toxic gas sensors [ 103 , 104 , 105 , 106 , 107 , 108 ]. Based on experimental evidence, the sensitivity and selectivity of doped graphene were higher than pristine graphene [ 103 , 104 , 105 , 106 , 107 ]. However, it is difficult to control the doping concentration and the number of graphene layers.…”
Section: Doped Graphenementioning
confidence: 99%